Cows Caught in the Crossfire: Provisional Remarks on India’s Current Cow-Slaughter Debate - Nadal, Deborah (Religions of South Asia, 2017)
This article focuses on the voices raised from Muslim, Christian and Dalit communities on the highly sensitive topic of beef consumption in India. It discusses the main points of the debate on cow protection which has taken place in the last years. India is defined as a secular country, but already in this text (in article 48) the hindu portion of the population managed to obtain an important recognition of the inviolability of the cow. as a matter of fact, the vast majority of Indian states (excluding the North-east states, West bengal and Kerala) currently forbid the slaughtering of cows, and often also of bulls, bullocks, heifers and calves. Many Muslims, Christians and Dalits, in addition to many people who work in the beef-related business, regard the constitutional immunity given to the cow as discriminating against their communities, through a sort of ‘food fascism’, not only from a religious point of view, but also in relation to their economical subsistence and livelihood.